Reproductive outcome in carrier couples of β-thalassemia disorders in a tertiary hospital in central India - Ranbir S. Balgir (Thalassemia Reports, 2014)
The β-thalassemia syndromes and hemoglobin disorders are the major genetic and public health challenges in Central India. In view of dubious credit of the highest infant mortality rate in Madhya Pradesh (62 as against 47 per 1000 live-births of India in 2011) it was presumed that carrier couples of b-thalassemia disorders might be one of the contributing factors to high mortality. A total of 280 couples including their offspring with at least one affected and/or suspected case of β-thalassemia/ sickle cell disorders referred to our Centre from a tertiary hospital, Jabalpur during March 2010 to February 2013 were consecutively studied as matched case controls. Out of 280 couples, 200 were found normal and 80 couples had different b-thalassemia disorders. β-thalassemia carrier couples had significantly higher relative fertility (mean number of conceptions, i.e. 2.457 versus 1.480), higher infant mortality (3.5% versus 1.3%), higher below 10 years mortality (7.0% versus 2.7%) and lower surviving offspring (925.9 versus 970.6) than of controls. Still-births were three times lower (12.3), neonatal deaths almost two folds higher (24.7), three folds higher infant mortality (37.0) and almost three times higher below 10 years mortality per 1000 live-births were observed in carriers of β-thalassemia major than in controls. The present study indicated that afflicted couples of these hereditary disorders are increasing the afflicted offspring, being 60.7% surviving against controls (39.3%). This increased production of afflicted (heterozygous and homozygous) offspring leads to increased morbidity and mortality and might be contributing towards increased neonatal/infant mortality in Madhya Pradesh of Central India. As a preventive measure, affected families were imparted genetic/marriage counseling.     β-重型地中海贫血综合征和血红蛋白疾患是印度中部地区主要的基因以及公共卫生挑战。据不确切数据，印度中央邦新生儿的死亡率最高（1000新生儿中有62例死亡，对比2011全印度平均值47例）。据此认为，患有β-重型地中海贫血的新生儿夫妇是导致其高死亡率的主要原因之一。从2010年3月至2013年2月，位于贾巴尔普尔（印度中部城市）的一家三级医院，针对了280对夫妇及他们的后代（每对夫妇中，至少有一位确认或疑似患有β-重型地中海贫血症）进行了这项近三年的研究。在这280对夫妇中，200对正常，80对患有不同类型的β-重型地中海贫血紊乱症。 β-地中海贫血载体夫妇对比接受治疗控制的夫妇，有相对较高的生育力（i.e.平均值2457 ：1480），更高的婴儿死亡率（3.5% ：1.3%），更高的10岁以下死亡率（7% ：2.7%）以及较低的后代存活率（925.9 ：970.6）。β-重型地中海贫血患者夫妇对比接受治疗控制的夫妇，死产数低于三倍（12.3），新生儿死亡数高于2倍（24.7），高于三倍的婴儿死亡数（37.0）以及近3倍的10岁以下死亡数。目前研究表明，患有该遗传疾病的夫妇也增加了他们后代的患病率，60.7%对比39.3%（正常值）。随着患者夫妇后代人数的增加，这些后代也会加剧印度中央邦新生儿和婴儿的死亡率。作为一项预防措施，受到影响的家庭被建议接受有关遗传和婚配的咨询。